Manajemen Kesiswaan Di Sekolah Dasar Islam Mohammad Hatta Di Masa Pandemi Covid-19 - Alfin Nur Zakiyah (STAI Ma'had Aly Al-Hikam Malang, 2021)
The covid-19 pandemic has had an impact on various aspects of life. With various new policies taken regarding the Covid-19 pandemic, new adaptations are needed for our lives. The existence of the PSBB policy (large-scale social restrictions), social distancing and stay at home forced everyone during this pandemic to carry out all activities from home on an online basis. Likewise in the education sector, which must adapt to new habits related to policies during the Covid-19 pandemic. This research was conducted with the aim of knowing student management at the Mohammad Hatta Islamic Elementary School during the Covid-19 pandemic based on research. This research is a case study research using a descriptive qualitative research approach to describe the findings obtained after the research. The data in this study were collected by means of interviews, observation and documentation study. The research results show that in a managerial system, the activities in this institution have been systematically organized even though they are still adapting to the latest policy updates from the government. This institution strives to continue to optimize student activities amidst the limitations of meeting face to face.